Managing advanced HR-positive, HER2-negative breast cancer with CDK4/6 inhibitors in post-menopausal patients: is there a best sequence?. (December 2018) - Rossi, Lorenzo; McCartney, Amelia; Risi, Emanuela; Malorni, Luca; Biganzoli, Laura; Di Leo, Angelo
The current therapeutic landscape of luminal human epidermal growth factor receptor 2 (HER2)-negative metastatic breast cancer (mBC) is fundamentally evolving, particularly in the advent of molecularly targeted therapies, such as inhibitors of mammalian target of rapamycin and cyclin-dependent kinase 4/6 (CDK4/6). In the context of CDK4/6 inhibitors, landmark clinical trials for palbociclib (PALOMA-1, PALOMA-2, PALOMA-3), ribociclib (MONALEESA-2, MONALEESA-3, MONALEESA-7) and abemaciclib (MONARCH-1, MONARCH-2, MONARCH-3) have provided solid data regarding progression-free survival and overall response rate, justifying the introduction of this class of drugs into our therapeutic armoury. However, several clinical questions remain open. One of the most relevant issues faced in practice is that of the optimum sequencing of CDK4/6 inhibitors, particularly given the wide range of therapeutic options open to clinicians treating luminal mBC. In this brief commentary, we would like to focus on the best sequence for CDK4/6 inhibitors and their place in this growing, complex scenario.